Recruiting and retaining girls in table tennis: Participant and club perspectives. Issue 5 (November 2018) - Rowe, Katie; Sherry, Emma; Osborne, Angela
Highlights: Low profile sports including table tennis face challenges in recruiting and retaining girls. Girls' participation in table tennis is constrained by a male dominated club culture. Other social factors further limit girls' participation. Table tennis stakeholders may benefit from strategically addressing such issues. Abstract: Government and sport stakeholders, in the Australian context, are focused on increasing girls' participation in sport. Sport organisations, particularly those who receive limited government funding and commercial revenue, experience challenges in recruiting and retaining adolescent girls. In this paper, a case study of table tennis delivery in one Australian state, is presented, with a focus on the issue of girls' participation. Framed using Green's (2005) normative theory of sport development, and drawing on physical activity participation literature, micro- and meso-level factors are examined. The focus is placed on girls' experiences participating in the sport of table tennis and how delivery stakeholders find the process of recruiting and retaining girls in the sport. Interviews and focus groups reveal that a male-dominated culture, resource constraints, and a host of social influences, including peer and parental influences, and the absence of a social norm around girls' participation, are hampering this sport's capacity to recruit and retain adolescent females. Organisational commitment at state and national levels are necessary if table tennis is to target the issue of gender balance within its junior participation market.